Heart Valves From Design to Clinical Implantation - Iaizzo, Paul A.; Bianco, Richard W.; Hill, Alexander J.; St. Louis, James D. (Springer US : Imprint: Springer, 2013)
Cardiovascular disease is the major cause of morbidity and mortality worldwide. While the past 40 years have brought major progress in cardiac valve repair and replacement, there remain large patient populations that do not receive such therapies. This, in turn, implies a great need for future basic, applied, and clinical research and, ultimately, therapeutic developments. Heart Valves is a state-of-the-art handbook dedicated to: 1) cardiac valve anatomy, 2) models for testing and research methods; 3) clinical trials; and 4) clinical needs and applications.